Optimalisasi sistem plumbing hemat air di Rusun Brimob Sampali Medan: edukasi teknologi dan manajemen limbah cair - Siregar, Zufri Hasrudy; Nasution, Arif Fadillah; Mawardi; Puspita, Riana; Refiza; Nasution, Asmara Sari; Fazri, Muhammad; Lubis, Saidan Sany (LPPM Universitas Al-Azhar medan, 2025)
The availability of clean water in high-density urban areas is a pressing concern, as evidenced by the limited infrastructure and significant water wastage, which can reach 30%. This research aims to optimize the water-saving plumbing system in Brimob Sampali Flat in Medan through an integrative approach of applying modern technology and community education.This research utilizes a mixed method of qualitative (observation, interview) and quantitative (Likert scale questionnaire, digital measurement) data collection. The research process is outlined as follows: first, the existing conditions are analyzed; second, a new plumbing system is designed; third, water-saving technologies are implemented, such as gray water recycling systems and dual flush toilets; fourth, the effectiveness of the system is monitored and evaluated.The study population consisted of 30 residents of the Brimob Sampali Flat in Medan, and their pre- and post-implementation water consumption data were compared to measure the impact of the system.The results indicated that the implementation of the water-efficient plumbing system led to a 33.52% reduction in water consumption, while the integration of the gray water recycling system augmented this reduction by an additional 58.17%.The educational program was found to have enhanced residents' comprehension of water conservation, as evidenced by an average Likert score of 4.03 out of 5. Moreover, satisfaction with the novel system attained an average score of 4.1, signifying a positive response.The novelty of this study lies in the integration of water-saving technologies with an educational program designed specifically for the local Indonesian context, providing a holistic model that can be replicated in other regions to address clean water issues in a sustainable manner.